Emotive media - A review of emotional interfaces and media in human-computer-interaction - Lugmayr, Artur (2016)
Emotive Media - thus media environments and interfaces responding and understanding human bio-feedback data can be considered as a new paradigm in the wider field of human-computer-interaction. The emergence of consumer priced bio-feedback devices, such as brain interfaces, biometric sensors, or health monitoring lead the pathway to new possibilities in human-computer interaction, and the creation of consumer experiences. The goal of this paper is to define categories for emotive media, present application scenarios, and introduce emotive media as a paradigm in human-computer-interaction.